Moderasi Beragama dan Media Sosial (Studi Analisis Konten Instagram & Tik-Tok) - Putri Septi Pratiwi; Mia Putri Seytawati; Ahmad Fauzan Hidayatullah; Ismail Ismail; Tafsir Tafsir (Institut Agama Islam Negeri (IAIN) Curup, 2021)
This article is prepared to examine some of the references as a foundation for describes the influence of social media as a medium for campaigning related to religious moderation movements and conceptualizes the form of the use of Instagram and Tiktok social media in campaigning for religious moderation movements. The method used in the preparation of this journal is qualitative descriptive combined with literature review research on related sources and journals, the research approach used is a field study, with a focus on the study of Instagram and Tik Tok content. Religious moderation is a moderate view or attitude to try to take a neutral or middle position against the diversity of beliefs. With the existence of religious moderation, it is hoped that a balance in religion will be created. To strengthen religious moderation, various strategies can be carried out, one of the strata is the socialization of ideas, understanding, and education regarding religious moderation to the whole society. Because of this, the campaign regarding the religious moderation movement must be carried out massively and synergistically, especially on social media, especially Instagram and TikTok, which are social media services that are currently popular recently. By utilizing the popularity of social media networking services, it is hoped that the campaign against the religious moderation movement will be well received by the public. Because of this, the campaign regarding the religious moderation movement must be carried out massively and synergistically, especially on social media, especially Instagram and TikTok, which are social media services that are currently popular recently. By utilizing the popularity of social media networking services, it is hoped that the campaign against the religious moderation movement will be well received by the public. Because of this, the campaign regarding the religious moderation movement must be carried out massively and synergistically, especially on social media, especially Instagram and TikTok, which are social media services that are currently popular recently. By utilizing the popularity of social media networking services, it is hoped that the campaign against the religious moderation movement will be well received by the public.